The Influence of Work Motivation, Principal Leadership, Work Environment, Gender, and Technological Proficiency on Teacher Performance at Tiara School Jakarta: A Total Quality Management Orientation - Abdul Canter Sangaji; R. Madhakomala (LP2M IAIN Palopo, 2025)
This study aims to examine the influence of work motivation, principal leadership, work environment, gender, and technological proficiency on teacher performance at Tiara School Jakarta within the framework of Total Quality Management (TQM). Using a quantitative approach with a causal associative design, this research involved all 35 teachers as the total sample. Data were collected through a structured questionnaire and analyzed using multiple linear regression. The results reveal that work motivation and technological proficiency have a positive and significant effect on teacher performance, with technological proficiency emerging as the most dominant factor. Conversely, principal leadership and work environment show a positive yet insignificant influence, while gender does not contribute significantly to performance differences. These findings emphasize that strengthening intrinsic motivation and digital competency is essential for enhancing teacher performance, especially in a TQM-oriented school environment. The implication of this study highlights the importance of continuous professional development, digital training, and quality-centered leadership as strategic efforts to improve educational quality in modern schools.